Management of Scientific Journals At State Islamic Religious College (PTKIN) and Lecturer Career Development in North Sumatra - Yusnaili Budianti; Hasan Asari; Hafsah Hafsah (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This study aimed to map journal management issues at State Islamic Religious College (PTKIN) in North Sumatra. It used the descriptive qualitative method, focusing on journal institutions and rankings, financing, coaching activities, and improving lecturer careers. Data were collected using observation, a document study, FGDs with journal managers, lecturers, and structural leaders, and analyzed using an interim analysis from McMillan and Schumacher. The results showed that the scientific journal management at State Islamic University (UIN) in North Sumatra varied, and most did not fulfill the National Journal Accreditation (Arjuna) standards. It has not fully referred to the standard guidelines for journal management, and only 25% have been accredited. Furthermore, budget allocation is limited but improving. There are several coaching activities, including increasing the competence of journal management resources through training and workshops and maximizing the function of the Academic Writing Center (AWC). The coaching activities also include improving lecturer rank database, assistance in writing and publishing articles, socializing techniques for calculating lecturer credit scores, and cooperation between Indonesia’s PTKIN and foreign colleges. The journal development activities have not been maximized in supporting lecturer careers. Most lecturers at State Islamic University of North Sumatra have the rank of Lecturer and Head Lecturer and face difficulties advancing their careers. Therefore, it is necessary to formulate effective ways to link journal development and smooth promotion of lecturers.